Prospects of Development of Domestic Engineering-Pedagogical Education in the Context of European Integration Processes - Viktoria Bilyk (Pedagogical Discourse, 2012)
Сharacteristic of the status and main directions of development of higher professional education in conditions of Eurointegration processes is offered. The  problems and ways of reforming of modern engineering-pedagogical education are studied.